Expulsion of a uterine myoma in a patient treated with ulipristal acetate. Issue 4 (2nd February 2015) - Chantraine, Frederic; Poismans, Gaelle; Nwachuku, Julia; Bestel, Elke; Nisolle, Michelle
Key Clinical Message Description of a spontaneous expulsion of a submucosal myoma in a patient treated with ulipristal acetate.